AGRESIVITAS ANAK KORBAN EKSPLOITASI KECAMATAN SAIL KELURAHAN CINTA RAJA PEKANBARU - Ramaini, Sari; Umari, Tri; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the description of the forms of aggressiveness experienced by children victims of exploitation, the aggresiveness of children of victims of exploitation and factors that affect children of victims of exploitation behave aggressively. The subjects in this study were children of victims of exploitation who were under eighteen years old, but had worked on the streets located in the Sail Sub district of Cinta Raja Pekanbaru. The study was conducted with a qualitative approach and type of descriptive research and the data obtained in the study were sourced from the results of structured observations and interviews. The result of the study explained that there are still many children victims of exploitation who receive aggressive treatment, and also found that some of them behave agrressively towards others. Other than that there are things that are a factor of child victims of exploitation behaving aggressively.Key Words: Aggressiveness, child of exploitation